Sport-2-Stay-Fit study: Health effects of after-school sport participation in children and adolescents with a chronic disease or physical disability - Zwinkels, Maremka (BMC Sports Sci Med Rehabil, 2015)
BACKGROUND: Children and adolescents with a chronic disease or physical disability have lower fitness levels compared to their non-disabled peers. Low physical fitness is associated with reduced physical activity, increased cardiovascular diseases, and lower levels of both cognitive and psychosocial functioning. Moreover, children and adolescents with a chronic disease or physical disability participate less in both recreational and competitive sports. A variety of intervention studies have shown positive, but only temporary, effects of training programs. Next to issues related to the chronic condition itself, various personal and environmental factors play a key role in determining the extent to which they participate in sports or physical activities. Due to these barriers, sport participation in the immediate after-school hours seems to be a feasible solution to get these children and adolescents physical active structurally. To investigate if an after school sport program can sustain the positive effects of an intervention, a standardized interval training will be given to improve physical fitness levels. High-intensity Interval Training (HIT) is superior to moderate-intensity continuous training in improving physical fitness in patients with chronic diseases. Therefore, the Sport-2-Stay-Fit study will investigate whether after school sport participation can increase the sustainability of a HIT program in children and adolescents with a chronic disease or physical disability. METHODS: The Sport-2-Stay-Fit study is a clinical controlled trial. A total of 74 children and adolescents in the age of 6–19 years with a chronic disease or physical disability will be included. This could be either a cardiovascular, pulmonary, metabolic, musculoskeletal or neuromuscular disorder. Both children and adolescents who are ambulatory or propelling a manual wheelchair will be included. All participants will follow a HIT program of eight weeks to improve their physical fitness level. Thereafter, the intervention group will participate in sport after school for six months, while the control group receives assessment only. Measurements will take place before the HIT, directly after, as well as, six months later. The primary objective is anaerobic fitness. Secondary objectives are agility, aerobic fitness, strength, physical activity, cardiovascular health, cognitive functioning, and psychosocial functioning. DISCUSSION: If effective, after school sport participation following a standardized interval training could be implemented on schools for special education to get children and adolescents with a chronic disease or physical disability active on a structural basis. TRIAL REGISTRATION: This trial is registered at the Dutch Trial Register #NTR4698.